Preparation method of iron-based amorphous and nanocrystalline

Through laser etching and heat treatment technology, the grains of iron-based amorphous and nanocrystalline magnetic cores are refined, which solves the problem of the inductance of the magnetic core dropping under saturation state, improves the anti-saturation ability and magnetic permeability of the magnetic core, and meets high efficiency Inductance requirements.

CN115351429BActive Publication Date: 2024-12-27宁波中益赛威新材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211123745.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-15
Publication Date
2024-12-27
Estimated Expiration
2042-09-15

AI Technical Summary

Technical Problem

The inductance of existing iron-based amorphous and nanocrystalline magnetic cores rapidly declined under saturation, which could not effectively suppress interference, especially in the DC current loop, which could no longer cause magnetic flux changes, resulting in inductor failure.

Method used

The iron-based amorphous and nanocrystal strips with preset patterns are wound into magnetic rings by laser etching, and preheating and magnetic field heat treatment are performed to excite uniformly distributed nuclei and refined grains, and the nucleation and grain length are controlled separately. The large process improves the magnetic permeability and saturation resistance of the magnetic core.

Benefits of technology

By refining the grains and improving the permeability, the anti-saturation capability of the magnetic core is significantly improved, ensuring that the core is unsaturated when the instantaneous high current flows through the coil, meeting the needs of high-efficiency inductance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115351429B_ABST
    Figure CN115351429B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing iron-based amorphous and nanocrystalline materials, and belongs to the technical field of magnetic materials. The invention uses laser etching to form a preset pattern on the surface of an iron-based amorphous and nanocrystalline strip, and winds the iron-based amorphous and nanocrystalline strip carrying the preset pattern into a magnetic ring of a preset size; firstly, the magnetic ring is preheated to stimulate the iron-based amorphous and nanocrystalline materials to form high-density and uniformly distributed crystal nuclei; then, the magnetic ring after the preheating treatment is subjected to magnetic field heat treatment to make the grains in the iron-based amorphous and nanocrystalline materials grow synchronously, and the competition between the grains is used to promote the grain refinement, and the magnetic ring after the magnetic field heat treatment is placed in a protective box matching the size of the magnetic ring for packaging to obtain an iron-based amorphous and nanocrystalline magnetic core.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic materials, and in particular to a method for preparing an iron-based amorphous and nanocrystalline magnetic core. Background Art

[0002] The arrangement of atoms in iron-based amorphous and nanocrystalline materials is macroscopically chaotic and disordered. Due to their special structure and excellent comprehensive soft magnetic properties, they can be used to manufacture various medium and high frequency transformers, high-performance inductors, filters, sensors and other devices. They can also be used in high-precision electromagnetic measurement, high-performance electromagnetic shielding, and the preparation of absorbing materials. Because amorphous and nanocrystalline materials also have efficient preparation processes and excellent material properties, amorphous alloys are gradually replacing traditional soft magnetic materials such as silicon steel, Permalloy and ferrite, and are gaining more and more applications in the fields of electricity, electronics, and communications.

[0003] The existing iron-based amorphous, nanocrystalline or other magnetic cores in inductors can take advantage of their high magnetic permeability to increase inductance, reduce the number of turns, reduce volume and improve efficiency. However, due to the limitations of the physical structure of magnetic materials, the magnetic flux passing through the existing iron-based amorphous and nanocrystalline magnetic cores is limited and cannot be increased infinitely. When the magnetic flux passing through the magnetic material reaches a certain value, it will no longer increase. Even if the current or the number of turns is increased, the magnetic core is still in a state of magnetic saturation. Especially in a DC current loop (such as: a coil flowing through an instantaneous large current), if the DC current has saturated the magnetic core, the AC component in the current will no longer cause a change in the magnetic flux, and the inductor will lose its function. Summary of the invention

[0004] Aiming at the problem that the inductance of the existing iron-based amorphous and nanocrystalline magnetic cores drops rapidly after being in a saturated state and interference cannot be suppressed, a method for preparing an iron-based amorphous and nanocrystalline magnetic core is provided to improve the anti-saturation ability of the magnetic core.

[0005] The present invention provides a method for preparing an iron-based amorphous and nanocrystalline material, comprising:

[0006] Laser etching is used to form a preset pattern on the surface of the iron-based amorphous and nanocrystalline strips;

[0007] Winding the iron-based amorphous or nanocrystalline strip carrying the preset pattern into a magnetic ring of preset size;

[0008] Preheating the magnetic ring to stimulate the iron-based amorphous and nanocrystalline materials to form uniformly distributed crystal nuclei;

[0009] Performing magnetic field heat treatment on the preheated magnetic ring to refine the grain growth in the iron-based amorphous and nanocrystalline materials;

[0010] The magnetic ring after the magnetic field heat treatment is installed in a protective box matching the size of the magnetic ring for packaging to obtain an iron-based amorphous and nanocrystalline magnetic core.

[0011] Optionally, the iron-based amorphous and nanocrystalline strip includes a roller surface and a free surface, the roller surface is the surface close to the copper roller when the iron-based amorphous and nanocrystalline strip is formed, and the free surface is the surface away from the copper roller when the iron-based amorphous and nanocrystalline strip is formed, and the preset pattern is formed on the free surface.

[0012] Optionally, the etching depth of the preset pattern ranges from 0.4 times to 0.8 times the thickness of the iron-based amorphous or nanocrystalline strip.

[0013] Optionally, the etching depth of the preset pattern is 0.6 times the thickness of the iron-based amorphous and nanocrystalline strip.

[0014] Optionally, the preset shape is any one of a circle, a square, a hexagon, and an octagon.

[0015] Optionally, the preheating of the magnetic ring includes:

[0016] The annealing temperature range of the preheating treatment is 400° C. to 500° C., the holding time range is 10 min to 60 min, and the cooling temperature range is 300° C. to room temperature.

[0017] Optionally, the magnetic field heat treatment of the magnetic ring after the preheat treatment includes:

[0018] The first heating temperature range of the magnetic field heat treatment is 400°C to 500°C, the insulation time range is 40min to 180min, the second heating temperature range is 500°C to 600°C, the insulation time range is 60min to 480min, and the cooling temperature range is 300°C to room temperature.

[0019] Optionally, the magnetic ring after the magnetic field heat treatment is placed in a protective box matching the size of the magnetic ring for packaging to obtain iron-based amorphous and nanocrystalline, including:

[0020] The magnetic ring after magnetic field heat treatment is installed in a protective box that matches the size of the magnetic ring, and the protective box containing the magnetic ring is seamlessly welded by laser welding. The magnetic ring in the protective box is broken up along the path of the preset pattern by pulse vibration, so that an air gap is formed inside the magnetic core, thereby generating an iron-based amorphous and nanocrystalline magnetic core.

[0021] Beneficial effects of the above technical solution:

[0022] In the technical scheme, the preparation method of the iron-based amorphous and nanocrystalline magnetic core uses laser etching to form a preset pattern on the surface of the iron-based amorphous and nanocrystalline strip, and the iron-based amorphous and nanocrystalline strip carrying the preset pattern is wound into a magnetic ring of a preset size; the magnetic ring is first preheated to stimulate the iron-based amorphous and nanocrystalline materials to form high-density and uniformly distributed crystal nuclei; the magnetic ring after the preheating treatment is subjected to magnetic field heat treatment to make the grains in the iron-based amorphous and nanocrystalline materials grow synchronously, and the competition between the grains is used to promote the grain refinement, and the magnetic ring after the magnetic field heat treatment is placed in a protective box matching the size of the magnetic ring for packaging to obtain an iron-based amorphous and nanocrystalline magnetic core. Compared with the existing heat treatment method, the present application adopts a two-step heat treatment method to separately control the nucleation and grain growth process of the iron-based amorphous and nanocrystalline magnetic core, thereby effectively improving the grain density and crystallinity, and then improving the size and uniformity of the grains, refining the grains, greatly improving the magnetic permeability of the magnetic core, and reducing the loss. The iron-based amorphous and nanocrystalline magnetic core of the present application has a high anti-saturation capability and can meet the requirement that the magnetic core is not saturated when a large instantaneous current flows through the coil. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A method flow chart of an embodiment of the method for preparing the iron-based amorphous and nanocrystalline magnetic core according to the present invention;

[0024] Figure 2 It is a schematic diagram of the preparation process of the iron-based amorphous and nanocrystalline magnetic cores of the present invention;

[0025] Figure 3 It is a schematic diagram of the process curve of the preheating treatment and magnetic field heat treatment of the present invention;

[0026] Figure 4 It is a schematic diagram of the comparison line curve of the magnetic core hysteresis loop. DETAILED DESCRIPTION

[0027] The advantages of the present invention are further described below in conjunction with the accompanying drawings and specific embodiments.

[0028] Exemplary embodiments will be described in detail herein, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, the same numbers in different drawings represent the same or similar elements unless otherwise indicated. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present disclosure. Instead, they are merely examples of devices and methods consistent with some aspects of the present disclosure as detailed in the appended claims.

[0029] The terms used in the disclosure of this application are only for the purpose of describing specific embodiments, and are not intended to limit the disclosure of this application. The singular forms of "a", "said" and "the" used in the disclosure of this application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used in this article refers to and includes any or all possible combinations of one or more associated listed items.

[0030] It should be understood that although the terms first, second, third, etc. may be used to describe various information in the present disclosure, these information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of the present disclosure, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Depending on the context, the word "if" as used herein may be interpreted as "at the time of" or "when" or "in response to determining".

[0031] In the description of the present invention, it should be understood that the numerical labels before the steps do not identify the order of executing the steps, but are only used to facilitate the description of the present invention and distinguish each step, and therefore cannot be understood as a limitation of the present invention.

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0034] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but they are not intended to limit the present invention.

[0035] See also Figure 1-Figure 2 As shown, this embodiment provides a method for preparing an iron-based amorphous and nanocrystalline magnetic core, comprising the following steps:

[0036] S1. Using laser etching to form a preset pattern on the surface of the iron-based amorphous and nanocrystalline strip;

[0037] The iron-based amorphous and nanocrystalline strips include a roller surface and a free surface. The roller surface (slightly dark surface gloss with copper roller surface texture) is the surface close to the copper roller when the iron-based amorphous and nanocrystalline strips are formed, and the free surface (bright surface gloss without copper roller surface texture) is the surface away from the copper roller when the iron-based amorphous and nanocrystalline strips are formed. The preset pattern is formed on the free surface. The roller surface is close to the cooling copper roller during preparation, and the cooling effect is relatively better than the free surface. Although the thickness of the iron-based amorphous and nanocrystalline strips is very thin (micrometer level), there is still a difference in surface toughness. Compared with the free surface far away from the cooling roller, the toughness is greater than the roller surface.

[0038] In this embodiment, a laser is used to etch a preset pattern (i.e., a texture path) with controllable depth and variable pattern along the surface of the iron-based amorphous or nanocrystalline strip. As an example but not limitation, the preset pattern can be any one of a circle, a square, a hexagon, and an octagon.

[0039] Furthermore, the etching depth of the preset pattern ranges from 0.4 times to 0.8 times the thickness of the iron-based amorphous and nanocrystalline strips.

[0040] In this embodiment, the etching depth is the biggest factor affecting the winding of the magnetic core. If the depth exceeds 0.8 times the thickness of the iron-based amorphous and nanocrystalline material, the material will break and cannot be wound with constant tension. If the depth is less than 0.4 times the thickness of the iron-based amorphous and nanocrystalline material, the vibration fragmentation after heat treatment is incomplete, affecting the anti-saturation ability of the magnetic core. Therefore, the etching depth needs to be between 0.4 and 0.8 times the thickness of the iron-based amorphous and nanocrystalline strip.

[0041] In a preferred embodiment, the etching depth of the preset pattern is 0.6 times the thickness of the iron-based amorphous and nanocrystalline strip, but is not limited to this depth; using this depth allows the core to be wound with the stick facing outward and the free surface facing inward in a clockwise direction, thereby avoiding the risk of material breakage when the core is wound with constant tension.

[0042] S2. Winding the iron-based amorphous or nanocrystalline strip carrying the preset pattern into a magnetic ring of preset size.

[0043] In this embodiment, the etched iron-based amorphous and nanocrystalline strips can be wound into a magnetic ring of a certain size according to actual needs.

[0044] S3. Preheating the magnetic ring to stimulate the iron-based amorphous and nanocrystalline materials to form uniformly distributed crystal nuclei;

[0045] In this embodiment, after the surface of the iron-based amorphous and nanocrystalline material is laser-etched with a preset pattern, the etching path causes the original relatively balanced mechanical stress between the free surface and the stick surface to be broken. In order to eliminate the material stress and moderately change the crystalline structure to restore and improve the magnetic properties of the magnetic core, this embodiment is based on the iron-based amorphous and nanocrystalline material using a preheating method (see Figure 3 ), rapid heating and short-term heat preservation are carried out to stimulate the material to form high-density, evenly distributed crystal nuclei.

[0046] Furthermore, the preheating treatment of the magnetic ring includes: the annealing temperature range of the preheating treatment is 400°C to 500°C, the holding time range is 10min to 60min, and the cooling temperature range is 300°C to room temperature.

[0047] Specifically, see Figure 3 As shown, the process of preheating the magnetic ring (i.e. Figure 3 1-3) are as follows: heating from 100°C to 400°C-500°C, the heating time range is 10min-60min, the annealing temperature range is 400°C-500°C, the holding time range is 10min-60min, and then cooling to 200°C, the cooling time range is 10min-60min.

[0048] S4. Performing a magnetic field heat treatment on the preheated magnetic ring to refine the grain growth in the iron-based amorphous and nanocrystalline materials;

[0049] In this embodiment, the magnetic field heat treatment is performed on the preheated magnetic ring, which can make the high-density grains grow synchronously, and the competition between the grains is used to promote grain refinement. Compared with the existing conventional heat treatment methods, the present application separately controls the nucleation and grain growth processes of iron-based amorphous and nanocrystalline crystallization, improves the grain density, crystallinity, grain size and distribution uniformity, and refines the grains, greatly improves the magnetic permeability of the magnetic core, and reduces losses.

[0050] Furthermore, the magnetic field heat treatment of the magnetic ring after preheating treatment includes: the first heating temperature range of the magnetic field heat treatment is 400℃~500℃, the insulation time range is 40min~180min, the second heating temperature range is 500℃~600℃, the insulation time range is 60min~480min, and the cooling temperature range is 300℃~room temperature.

[0051] Specifically, see Figure 3 As shown, the process of magnetic field heat treatment of the magnetic ring (i.e. Figure 33-9) are as follows: heating the magnetic ring from 200°C to 400°C-500°C, the heating time range is 10min-60min, the first heating temperature range is 400°C-500°C, and the insulation time range is 40min-180min; heating the magnetic ring again to 500°C-600°C, the heating time range is 10min-60min, the second heating temperature range is 500°C-600°C, the insulation time range is 60min-480min, and then cooling to 200°C, and a transverse magnetic field is synchronously applied to the magnetic core in the furnace during the insulation time of the second heating temperature to the cooling time, the magnetic field current is 20-80A, and the cooling time range is 10min-60min.

[0052] S5. The magnetic ring after the magnetic field heat treatment is placed in a protective box matching the size of the magnetic ring for packaging to obtain an iron-based amorphous or nanocrystalline magnetic core.

[0053] Further, step S5 may include:

[0054] The magnetic ring after magnetic field heat treatment is installed in a protective box that matches the size of the magnetic ring, and the protective box containing the magnetic ring is seamlessly welded by laser welding. The magnetic ring in the protective box is broken up along the path of the preset pattern by pulse vibration, so that an air gap is formed inside the magnetic core, thereby generating an iron-based amorphous and nanocrystalline magnetic core.

[0055] In this embodiment, a magnetic ring with qualified performance is installed in a protective box (plastic or specially specified material) of corresponding size. After the upper and lower covers of the protective box are buckled, a weld with moderate depth is left for inlaying welding wire. Laser technology is used to perform seamless welding along the weld of the protective box to ensure that the surface of the protective box is flat and smooth after welding, improve the overall strength of the protective box, and prevent the magnetic core from deforming during the process flow. After welding, the upper and lower covers of the protective box are a whole, ensuring the risk of leakage of magnetic core fragments when the protective box is cracked during vibration and fragmentation in the later process. At the same time, the magnetic ring will not be displaced along the etching path, and the magnetic core will not be deformed. At the same time, the strength of the protective box is greatly improved to reduce the risk of deformation of the magnetic core winding and thus affect the product performance. Through pulse vibration, the magnetic ring after boxing is cracked and fragmented along the etching path in the protective box, but it does not displace, which promotes the formation of air gaps inside the magnetic core to obtain iron-based amorphous and nanocrystalline magnetic cores, so as to facilitate testing of whether the magnetic core meets the performance requirements according to requirements.

[0056] In this embodiment, the circumference of the etched preset pattern determines the size of the air gap after the iron-based amorphous and nanocrystalline materials are fragmented, thereby affecting the anti-saturation ability of the magnetic core. Under the same structure, more air gaps can increase energy storage, and the magnetic loss and iron loss are relatively reduced. The preset pattern determines the maximum length of the air gap, thereby reducing the residual magnetism of the magnetic core, reducing losses, and improving the anti-saturation ability. Table 1 is a table of experimental data of pulse vibration and heat treatment parameters of different preset patterns. Among them, Br represents the residual magnetism of the magnetic core, and Hc represents the coercive force (.

[0057]

[0058]

[0059] See also Figure 4 The horizontal axis B represents the magnetic saturation induction intensity of the magnetic core, and the vertical axis H represents the magnetization intensity of the magnetic core. The magnetic hysteresis loop comparison curve of the magnetic core is shown. The dotted line in the figure represents the conventional heat treatment method, and the solid line represents the preparation method of the iron-based amorphous and nanocrystalline in this embodiment. Figure 4 It can be seen that the lower the core remanence (Br) and coercive force (Hc), the smaller the area enclosed by the hysteresis loop, the lower the loss, the higher the flatness of the core magnetization curve and the closer it is to the H axis, the higher the core's anti-saturation ability.

[0060] The magnetic core performance of the nanocrystalline alloy prepared by the amorphous crystallization method in this application is greatly affected by the density of crystal nuclei in the strip. For conventional processes, this embodiment uses different heat treatment processes to separately control the crystallization nucleation and grain growth process of the iron-based nanocrystalline alloy in steps, improve the grain density and crystallinity of the nanocrystalline alloy material, and at the same time improve the uniformity of the grain size and distribution, refine the grains, thereby achieving the purpose of reducing the remanence and coercive force of the material and improving the comprehensive soft magnetic properties of the nanocrystalline material. Magnetic field heat treatment (magnetic field annealing) can change the chaotic arrangement of magnetic domains inside the material after conventional annealing, the irregular direction of the magnetic moment, and the phenomenon of whether some magnetic moments rotate during the magnetization process, so as to make the magnetic moment direction and the magnetic field direction distribution basically consistent.

[0061] In this embodiment, the method for preparing an iron-based amorphous and nanocrystalline magnetic core (eg Figure 2 As shown in the figure, a preset pattern is formed on the surface of an iron-based amorphous or nanocrystalline strip A by laser etching, and the iron-based amorphous or nanocrystalline strip carrying the preset pattern is wound into a magnetic ring B of a preset size; the magnetic ring B is first preheated to stimulate the iron-based amorphous or nanocrystalline material to form a high-density, uniformly distributed crystal nucleus; the magnetic ring B after the preheating treatment is subjected to a magnetic field heat treatment to make the grains in the iron-based amorphous or nanocrystalline material grow synchronously, and the competition between the grains is used to promote the grain refinement, so that the magnetic moment direction and the magnetic field direction are basically consistent, and the loss is reduced; the magnetic ring B after the magnetic field heat treatment is loaded into a protective box C matching the size of the magnetic ring for packaging to obtain an iron-based amorphous or nanocrystalline magnetic core D. Compared with the existing heat treatment method, the present application adopts a two-step heat treatment method to separately control the nucleation and grain growth process of the iron-based amorphous or nanocrystalline magnetic core, thereby effectively improving the grain density and crystallinity, and then improving the size and uniformity of the grains, refining the grains, greatly improving the magnetic permeability of the magnetic core, and reducing the loss. The iron-based amorphous and nanocrystalline magnetic core of the present application has a high anti-saturation capability and can meet the requirement that the magnetic core is not saturated when a large instantaneous current flows through the coil.

[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing an iron-based amorphous nanocrystalline magnetic core, characterized in that: include: Laser etching is used to form a preset pattern on the surface of the iron-based amorphous nanocrystalline strip; Winding the iron-based amorphous nanocrystalline strip carrying the preset pattern into a magnetic ring of preset size; Preheating the magnetic ring to stimulate the iron-based amorphous nanocrystalline material to form uniformly distributed crystal nuclei; Performing magnetic field heat treatment on the preheated magnetic ring to refine the grain growth in the iron-based amorphous nanocrystalline material; The magnetic ring after the magnetic field heat treatment is placed in a protective box matching the size of the magnetic ring for packaging to obtain an iron-based amorphous nanocrystalline magnetic core; The process of preheating the magnetic ring is as follows: heating from 100°C to 400°C-500°C, the heating time range is 10min-60min, the annealing temperature range is 400°C-500°C, the holding time range is 10min-60min, and then cooling to 200°C, the cooling time range is 10min-60min; The process of magnetic field heat treatment of the magnetic ring is as follows: heating the magnetic ring from 200°C to 400°C-500°C, the heating time range is 10min-60min, the first heating temperature range is 400°C-500°C, and the insulation time range is 40min-180min; heating the magnetic ring again to 500°C-600°C, the heating time range is 10min-60min, the second heating temperature range is 500°C-600°C, the insulation time range is 60min-480min, and then cooling to 200°C, and a transverse magnetic field is synchronously applied to the magnetic core in the furnace during the insulation time of the second heating temperature to the cooling time, the magnetic field current is 20-80A, and the cooling time range is 10min-60min.

2. The method for preparing an iron-based amorphous nanocrystalline magnetic core according to claim 1, characterized in that: The iron-based amorphous nanocrystalline strip includes a roller surface and a free surface. The roller surface is the surface close to the copper roller when the iron-based amorphous nanocrystalline strip is formed, and the free surface is the surface away from the copper roller when the iron-based amorphous nanocrystalline strip is formed. The preset pattern is formed on the free surface.

3. The method for preparing an iron-based amorphous nanocrystalline magnetic core according to claim 1, characterized in that: The etching depth of the preset pattern ranges from 0.4 times to 0.8 times the thickness of the iron-based amorphous nanocrystalline strip.

4. The method for preparing an iron-based amorphous nanocrystalline magnetic core according to claim 3, characterized in that: The etching depth of the preset pattern is 0.6 times the thickness of the iron-based amorphous nanocrystalline strip.

5. The method for preparing an iron-based amorphous nanocrystalline magnetic core according to claim 1, characterized in that: The preset shape is any one of a circle, a square, a hexagon, and an octagon.

6. The method for preparing an iron-based amorphous nanocrystalline magnetic core according to claim 1, characterized in that: The magnetic ring after the magnetic field heat treatment is placed in a protective box matching the size of the magnetic ring for packaging to obtain an iron-based amorphous nanocrystalline magnetic core, comprising: The magnetic ring after magnetic field heat treatment is installed in a protective box that matches the size of the magnetic ring, and the protective box containing the magnetic ring is seamlessly welded by laser welding. The magnetic ring in the protective box is broken into pieces along the path of the preset pattern through pulse vibration, so that an air gap is formed inside the magnetic core, thereby generating an iron-based amorphous nanocrystalline magnetic core.